Influenza vaccination and risk of atrial fibrillation in patients with gout: A nationwide population-based cohort study - Chen, Chun-Chao; Chiu, Chun-Chih; Chen, Nai-Hsuan; Yang, Tsung-Yeh; Lin, Cheng-Hsin; Fang, Yu-Ann; Jian, William; Lei, Meng-Huan; Yeh, Hsien-Tang; Hsu, Min-Huei; Hao, Wen-Rui; Liu, Ju-Chi (Frontiers in Pharmacology, 2022)
Objective: Although influenza vaccination reduces the risk of atrial fibrillation (AF), its protective effect in patients with gout remains unclear. The present study aimed to evaluate the protective effect of influenza vaccination in patients with gout. Methods: A total of 26,243 patients with gout, aged 55 and older, were enrolled from the National Health Insurance Research Database (NHIRD) between January 1, 2001, and December 31, 2012. The patients were divided into vaccinated (n= 13,201) and unvaccinated groups (n=13,042). After adjusting comorbidities, medications, sociodemographic characteristics, the risk of AF during follow-up period was analyzed. Results: In influenza, non-influenza seasons and all seasons, the risk of AF was significantly lower in vaccinated than in unvaccinated patients(Adjust hazard ratio [aHR]: 0.59, 95% confidence interval [CI]: 0.50-0.68; aHR: 0.50, 95% CI: 0.42-0.63; aHR: 0.55, 95% CI: 0.49-0.62, respectively). In addition, the risk of AF significantly decreased with increased influenza vaccination (aHR: 0.85, 95% CI: 0.69-1.04; aHR: 0.72, 95% CI: 0.60-0.87; aHR: 0.40, 95% CI: 0.33-0.49, after first, 2-3 times, and ≥ 4 times of vaccination, respectively). Furthermore, sensitivity analysis indicated that the risk of AF significantly decreased after influenza vaccination for patients with different sexes, medication histories, and comorbidities. Conclusions: Influenza vaccination is associated with a lower risk of AF in patients with gout. This potentially protective effect seems to depend on the dose administered.